Review of current tools and methods for REDD+ and REALU value chains - Bernard, F.; Minang, Peter A.; Noordwijk, Meine van (ASB Partnership, 2011)
In the context of the wider debate on reduction of carbon emissions from tropical deforestation and forest degradation, this report reviews current tools and methodologies for the planning of emissions reductions projects across all land uses in a REALU (Reducing Emissions from All Land Uses) value chain. This work supports Phase II of the REALU project, a joint effort of the ASB Partnership and several partner organizations. The overarching goal of this project is to develop, through action research, a set of approaches, methodologies and national capacity to implement effective landscape-based strategies for reducing emissions from deforestation and degradation (REDD+), within a context of sustainable rural development, national sovereignty, respect for indigenous rights, and integrity of a global Greenhouse Gas (GHG) accounting system.